Role of Cation-Anion Organic Ligands for Optical Properties of Fully Inorganic Perovskite Quantum Dots. (25th July 2018) - Forde, Aaron; Inerbaev, Talgat; Kilin, Dmitri
ABSTRACT: Application of lead-halide perovskite nanostructures for photovoltaic and light emitting applications depends on fashion of the surface termination. The reasonable choice of surface ligands for perovskite nanostructures prevent formation of trap states and contribute to chemical stability, wide opening of the bandgap, and intensity of absorption and photoluminescence of perovskite nanostructures. This work provides atomistic arguments for dual ligand protocol of surface passivation of fully inorganic perovskite quantum dots with fully organic ligands being a mix of cations (ethyl-ammonium) and anions (acetic) in nearly equal proportions. Computed binding energies of either individual ligands or anion-cation pairs demonstrate high stability in comparison to thermal energy and are concluded to be favourable choice in synthesis of colloidal perovskite quantum dots for light emitting applications.